Modulación de los niveles de lipoproteínas de alta densidad y las citoquinas il-1ß e il-6 en pacientes con dengue (2018)
Objectives. To assess High-Density Lipoprotein (HDL) and pro-inflammatory cytokine levels in patients with dengue classified according to the severity of the clinical presentation. Materials and Methods. A descriptive study was carried out with 70 individuals with dengue, classified as no alarm signs (DSSA), with signs of alarm (DCSA), and severe dengue (DG); 15 healthy donors were included as controls (CS). The serum levels of IL-1ß and IL-6 were quantified through ELISA, and the HDL levels through serum by a colorimetric test. In addition, the platelet count and the hematocrit percentage were determined. Results. Levels of IL-1ß and IL-6 were found to be increased in patients with DENV vs. the healthy controls. Said increase was more evident in patients with dengue and in line with the severity of the clinical presentation. The HDL levels were found to be decreased in patients with dengue versus healthy controls. The correlation analysis showed statistically significant associations between HDL and the platelet number, as well as between the hematocrit percentage and the levels of IL-1ß. Conclusions. The increased IL-1ß and IL-6 and the decreased HDL levels in the most severe clinical stages suggest that both factors are involved in the development of the pathogenesis and severity. The correlations allow the observation of a potential association between HDL and platelet count, which allows us to provide an approach to the possible role of HDL in the pathogenesis of dengue, but it is still necessary to perform additional studies that will allow to state their importance in the course of the DENV infection. © 2018, Instituto Nacional de Salud. All rights reserved.